ANALYSIS OF INNOVATIVE LEARNING AND SELF-EFFICACY ON TEACHER MOTIVATION WITH DIGITAL LITERACY AS AN INTERVENING VARIABLE INJUNIOR HIGH SCHOOL COUNTRY 1 PINTU RIME GAYO, BENER MERIAH REGENCY - Ida Fatimah; Elfitra Desy Surya; Mesra B (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of innovative learning and self-efficacy on teacher motivation, with digital literacy as an intervening variable at SMP Negeri 1 Pintu Rime Gayo, Bener Meriah Regency. Teacher motivation is a crucial factor in improving the quality of education, which can be influenced by teachers' ability to innovate, self-confidence in teaching, and skills in using digital technology. The approach used in this study was quantitative with the path analysis method. Data were collected through questionnaires distributed to all teachers at the school. The results showed that innovative learning and self-efficacy have a positive and significant effect on teacher motivation, both directly and through digital literacy as an intervening variable. Digital literacy has been shown to strengthen the relationship between learning innovation and self-efficacy on work motivation. These findings emphasize the importance of technology training and continuous teacher capacity development to improve professionalism and work enthusiasm in the school environment.